Dividend policy as an intervening variable between return on asset and earning per share on stock prices - Ari Kristin Prasetyoningrum; Kartika Marella Vanni; Anjar Mustika (Universitas Islam Negeri Walisongo Semarang, 2024)
Purpose - The aim of this study is to investigate how Return on Asset (ROA) and Earnings per Share (EPS) impact stock prices, while considering dividend policy as a mediating factor.Method - This research uses 6 samples of pharmaceutical companies listed on ISSI during the period of 2017-2021 using purposive sampling technique. The data analysis used in this research is SEM-PLS with the help of WarpPLS software version 7.0.Result - The findings indicate that dividend policy does not act as a mediator between ROA and share prices; however, it does serve as a mediator between EPS and share prices. The direct effects reveal that ROA has a non-significant positive impact on dividend policy, whereas EPS demonstrates a significant positive influence on dividend policy. Both ROA and dividend policy exhibit a significant negative impact on share prices, whereas EPS has a positive and significant influence on share prices. In addition, this research reveals that dividend policy is unable to mediate the relationship between ROA and share prices but is proven to mediate the relationship between EPS and stock prices.Implication - The concept of signaling theory in general can still be used in carrying out financial analysis even when anomalies occur in economic conditions.Originality - This research is research conducted on pharmaceutical companies which are different from other companies which have experienced negative impacts, but pharmaceutical companies have experienced an increase in share prices and profits during the pandemic.